2021
DOI: 10.1186/s12906-021-03272-8
|View full text |Cite
|
Sign up to set email alerts
|

Eye acupuncture for pain conditions: a scoping review of clinical studies

Abstract: Background Chinese eye acupuncture, focuses on treating different diseases by applying needle stimulation around the orbit of the eye. Since 1970, it has been used in China for the management of pain-related disorders. This scoping review systematically collected clinical studies on the use of eye acupuncture to treat pain conditions and identify any adverse events. Methods Six databases including PubMed, the Cochrane Library, CNKI, VIP, Wan Fang D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Since modern acupuncture, which is currently being practiced in several countries, emphasizes knowledge of eye anatomy and aseptic acupuncture, it is supposedly less likely to cause periocular adverse events. Periocular acupuncture is being performed worldwide for many ophthalmologic and nonophthalmologic conditions, such as headache, trigeminal neuralgia, neck stiffness, and acute lumbar sprain [17,26]. The incidence of complications, including perforation, is likely to increase as the acupuncture site is in close contact with the orbital margin.…”
Section: Managements and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since modern acupuncture, which is currently being practiced in several countries, emphasizes knowledge of eye anatomy and aseptic acupuncture, it is supposedly less likely to cause periocular adverse events. Periocular acupuncture is being performed worldwide for many ophthalmologic and nonophthalmologic conditions, such as headache, trigeminal neuralgia, neck stiffness, and acute lumbar sprain [17,26]. The incidence of complications, including perforation, is likely to increase as the acupuncture site is in close contact with the orbital margin.…”
Section: Managements and Discussionmentioning
confidence: 99%
“…Periorbital acupuncture was used not only for ophthalmologic diseases, but also for nonophthalmologic diseases, such as headaches, acute lumbar pain, and lumbar disc herniation, based on the theory of Traditional Chinese Medicine on the relationship among the eyes, brain, viscera, and meridians [ 26 ]. Moreover, “eye acupuncture” using the 13 acupuncture points around the eyes have been developed and studied since 1970, and the referred acupoints are the lung, large intestine, kidney, bladder, upper jiao, liver, gallbladder, middle jiao, heart, small intestine, spleen, stomach, and lower jiao ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of publications on acupuncture from Chinese institutions is increasing: according to a survey, studies from China accounted for 47% of the 13,320 acupuncture-related publications indexed in PubMed from 1995 to 2014 [10]. To avoid missing potentially relevant Chinese-language literature on acupuncture, many researchers have begun to search and include acupuncture studies in Chinese in their SR/MAs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, two systematic reviews [25,26] showed that KT had no significant effect on restenosis, recurrence of myocardial infarction, improvement of cardiac function, and reduction of adverse cardiovascular events in patients after PCI. acupuncture around the orbital margin is recognized as a sort of micro-acupuncture, which can activate the meridians, invigorate blood, relieve pain and regulate viscera functions by stimulating acupoints around the orbital margin [28,29]. According to the Meridian Theory of the Traditional Chinese Medicine [30,31], the tissue around the eye is closely related to the Zang and Fu organs, and acupuncture around the eye is effective in treating heart diseases.…”
Section: Introductionmentioning
confidence: 99%